Instillation of a Dry Powder in Nasal Casts: Parameters Influencing the Olfactory Deposition With Uni- and Bi-Directional Devices - Rigaut, Clément; Deruyver, Laura; Goole, Jonathan; Haut, Benoît; Lambert, Pierre (Frontiers in Medical Technology, 2022)
Nose-to-brain delivery is a promising way to reach the central nervous system with therapeutic formulations. However, the location of the olfactory region at the top of the nasal cavity complexifies this route of administration. In this study, we used a 3D-printed replica of a nasal cavity (a so-called “nasal cast”) to reproduce in vitro the deposition of a solid powder. We considered two different delivery devices: a unidirectional device generating a classical spray and a bidirectional device that relies on the user expiration. A new artificial mucus also coated the replica. Five parameters were varied to measure their influence on the powder deposition pattern in the olfactory region of the cast: the administration device, the instillation angle and side, the presence of a septum perforation and the flow rate of possible concomitant inspiration. We found that the classical powder spray is more effective in targeting the olfactory zone than the bi-directional device. Also, aiming the spray nozzle directly at the olfactory area is more effective than targetting the center of the nasal valve. Moreover, the choice of the nostril and the presence of a perforation in the septum also significantly influence the olfactory deposition. On the contrary, the inspiratory flow has only a minor effect on the powder outcome. By selecting the more efficient administration device and parameters, 44 % of the powder can reach the olfactory region of the nasal cast.